Update on the Management of Demodex Blepharitis. Issue 8 (3rd August 2022) - Shah, Paras P.; Stein, Rebecca L.; Perry, Henry D.
Abstract: Demodex blepharitis is a common ophthalmologic disease that is often overlooked in the workup of blepharitis. Demodex infestation occurs in both symptomatic and asymptomatic individuals at similar rates; consequently, its role in the development of blepharitis has not been well elucidated. Two species have been confirmed to inhabit the human eyelid— Demodex folliculorum and Demodex brevis. These species differ in their preferred location of infestation, with D. folliculorum occupying the base of the eyelash and D. brevis inhabiting the meibomian glands, contributing to anterior and posterior Demodex blepharitis, respectively. A clinical index of suspicion must be developed from the history when blepharitis, conjunctivitis, or keratitis in adults and blepharoconjunctivitis or chalazia in children are resistant to treatment. The diagnosis can be strongly suspected by the presence of cylindrical dandruff at the base of the eyelash and confirmed by light microscopy of an epilated lash or by in vivo confocal microscopy. No cure is currently available. Management most frequently includes topical tea tree oil and its active ingredient terpinen-4-ol, both of which have produced good clinical outcomes. Topical tea tree oil is typically applied by a professional due to risk of toxicity. Several second-line treatment options have been studied, including ivermectin, metronidazole, selenium sulfide, microblepharoexfoliation, and lid hygiene. Novel, targeted therapies such as TP-03 (Tarsus Pharmaceuticals) are also currently being investigated in phase 2b/3 clinical trials. The purpose of this review purpose is to characterize Demodex blepharitis in detail, including its historical perspective and various classifications, and describe the latest diagnostic and management strategies.